2015
DOI: 10.5713/ajas.15.0454
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Acceptability of Meat Nuggets with Fresh <i>Aloe vera</i> Gel

Abstract: Aloe vera has been used worldwide for pharmaceutical, food, and cosmetic industries due to its wide biological activities. However, quality improvement of low fat meat products and their acceptability with added Aloe vera gel (AVG) is scanty. The aim of this study was to explore the feasibility of using fresh AVG on physicochemical, textural, sensory and nutritive qualities of goat meat nuggets. The products were prepared with 0%, 2.5%, and 5% fresh AVG replacing goat meat and were analyzed for proximate compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…Ten grams of sample were macerated for 48 h in 80% ethanol at room temperature in the dark environment. Then, the samples were evaporated under vacuum at 40 °C until the solvent was removed (Rajkumar et al, 2016 ). In treatment III, Aloe vera gel was dried at 80 °C for 48 h. Then, 100 ml of deionized water was added to 10 ml of dried Aloe vera gel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten grams of sample were macerated for 48 h in 80% ethanol at room temperature in the dark environment. Then, the samples were evaporated under vacuum at 40 °C until the solvent was removed (Rajkumar et al, 2016 ). In treatment III, Aloe vera gel was dried at 80 °C for 48 h. Then, 100 ml of deionized water was added to 10 ml of dried Aloe vera gel.…”
Section: Methodsmentioning
confidence: 99%
“…Research on the use of Aloe vera in meat and meat products is quite new and limited research is available on this subject. In these limited number of studies, Aloe vera has been used in chicken meat (Meena et al 2019 ; Sari et al 2017 ), low-fat meat emulsion (Kumar et al 2017 ), low meat beef burgers (Soltanizadeh and Ghiasi-Esfahani 2015 ) and meat nuggets (Rajkumar et al 2016 ) for different purposes such as improving the quality and shelf-life. Sari et al ( 2017 ) showed that Aloe vera gel decreased cooking loss and fat absorption without adversly affecting the sensory properties in chicken meat during frying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are exploring various possibilities and combinations in search of different plant or seed extract having antioxidant, antimicrobial and other properties that maintain food safety and quality. Numerous studies have been aimed at assessing the effect of different plant materials on the oxidative deterioration of meat and meat products (Banerjee et al , 2012; Devatkal et al , 2010; Rajkumar et al , 2016; Shah et al , 2014; Singh et al , 2015; Tajkarimi et al , 2010; Tanwar et al , 2017). In this regard, black cumin extract (BCE) is important, as it possesses enormous biological properties and hence widely used in processed and pharmaceutical industries as well as in traditional therapeutic uses.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, aloe vera gel is sold commercially worldwide and is used as an ingredient in a wide range of food, cosmetic and therapeutic products [2] . It has recently been reported that incorporating aloe vera gel into emulsion-based goat meat nuggets enriches the functional value of the product [3] . Barbaloin (10-beta-D-glucopyranosyl-1,8-dihydroxy-3-(hydroxymethyl)-9(10H)-anthracenone) is considered the most specific extract of aloe [4] and has been reported to have a variety of pharmacological effects, including anti-inflammatory, antiviral, antibacterial, antitumor and free radicalscavenging effects [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%